2022
DOI: 10.3390/en15124477
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Color Temperature and Illuminance on Psychology, Physiology, and Productivity: An Experimental Study

Abstract: In this study, we investigated the impact of the lighting environment on psychological perception, physiology, and productivity and then designed lighting control strategies based on the experimental results. The research was conducted in a smart lighting laboratory, and 67 subjects were tested in different illuminances and correlated color temperatures (CCTs). During the experiment, the physiological data of subjects were continuously recorded, while the psychology and productivity results were evaluated by q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 68 publications
(58 reference statements)
1
11
1
Order By: Relevance
“…Some studies found that the heart rate of participants who remained in 6000 K lighting was slightly, but not significantly, higher than during the 2700 K period, regardless of whether it was day or night for the participants [ 52 , 53 , 54 ]. Conversely, other studies have found an increase in heart rate when CCT lighting conditions were higher [ 54 , 55 , 56 ], which is not consistent with the results of the present study. This may be due to the variability between CCT lighting conditions, the task scenarios set and the selection of the participant population.…”
Section: Discussioncontrasting
confidence: 99%
“…Some studies found that the heart rate of participants who remained in 6000 K lighting was slightly, but not significantly, higher than during the 2700 K period, regardless of whether it was day or night for the participants [ 52 , 53 , 54 ]. Conversely, other studies have found an increase in heart rate when CCT lighting conditions were higher [ 54 , 55 , 56 ], which is not consistent with the results of the present study. This may be due to the variability between CCT lighting conditions, the task scenarios set and the selection of the participant population.…”
Section: Discussioncontrasting
confidence: 99%
“…The Pearson analysis showed a correlation between relaxed-tense mood and CCT. This result was in line with the conclusion that CCT significantly affects the relaxed feeling (Chen, Tsai & Tsay, 2022). The negative coefficient on the result means that the warmer CCT, the subject will be more relaxed and the cooler the CCT will lead to a more tense mood.…”
Section: Discussionsupporting
confidence: 88%
“…Fourth, the spectral composition of light was not changed throughout the study. Moreover, neutral-white light was chosen for task lighting instead of cold-white light (6500 K or higher), as studies have shown that this light color is perceived as more pleasant 74 , 75 . However, it can be hypothesized that light pulses with high melanopic illuminance (i.e., with more short-wavelength radiation) could have even greater effects on attention.…”
Section: Discussionmentioning
confidence: 99%